EXPERIMENTAL RESULTS OF CURD CUTTING EQUIPMENT - Amgalanzul Jargalsaikhan; Damdinsuren Luvsansuren; Baatarkhuu Dorjsuren (World Science, 2022)
In order to cut the curd prepared in the traditional way in a short time and evenly, a curd cutting device was developed and the distance between the wires of the device was determined depending on the shrinkage coefficient of the curd. The cow's milk of a herder household in Tuv aimag is processed in the traditional way, yoghurt is prepared, the curd is placed on a yam cloth and pumped to a moisture content of 60%. Samples with the same amount of cut curd were dried in a desiccator at 50 ° C for 10 h and the weight and moisture content were determined every hour. As a result of the drying test, the weight of the curd stabilized after 7 hours, and the moisture content reached 20%, reaching the standard value. The linear size of the curds sampled after drying decreased by 16 to 23 percent and the linear shrinkage coefficient of the curds was 0.0274.